Sociopoetizando a participação na avaliação: os sentidos produzidos por alunos de uma escola pública - Costa, Hercilene Maria e Silva (2019)
This work presents the results of a master's research entitled SOCIOPOETIZATING THE PARTICIPATION IN ASSESMENT: THE MEANINGS PRODUCED BY STUDENTS OF A PUBLIC SCHOOL, which aimed to analyze the concepts that students have about student assessment and participation in school; and as specific objectives: mapping the concepts of students on their assessment and participation in school; to identify the problems that permeates their concepts of assessment and participation in school and that mobilize them; to understand other possibilities of thinking and/or problematize the student participation in school and the assessment; to identify the potential of students in the coping of problems related to their assessment and participation in school. The study is inserted in the axis of the school/student relationship, by monitoring the student segment. The study had as reference the theoretical conceptions of authors such as Barbier (1996), Barriga (1993), Baremblitt (1999), Esteban (2000, 2001), Vasconcelos (1970); and, as a theoretical-methodological framework, Sociopoetics - a research philosophical approach that uses art as a potential for the creation of confetti (concepts + affects). According to Gauthier (1995, 1999), Sociopoetics, beyond reason, encourages resorting to body, art and intuition in the production of knowledge. There were two researches in one, focusing on the themes of assessment and student participation in school. The locus of the investigation was the Barbara de Alencar Municipal Public School, located in Santa Maria Park, in Messejana, on the outskirts of Fortaleza. The two research groups were formed by the following subjects: in the research group of student participation in school (GP), students from 5th to 8th grades of the night shift; and; in the Assessment research group (GA); students from 1st to 4th grades of the afternoon shift. The investigation in both groups took place through workshops with sociopoetic experiences, through the so-called techniques, bridge to the imaginary, geomythical places, silent scenes/dynamic pictures, four elements, lying stories and story to continue. Among the metaphorical results of the research, we highlight some confections: in GP, the bridge/path presents itself as a metaphor of the difficulties and obstacles to student participation in school. At school/well the student is discredited and isolated, there is no student participation and his ideas are wasted, ignored. The tunnel/bridge is a state-to-state passage, the chiaroscuro, with possibilities to overcome obstacles. The school/tunnel is one that admits passages and exchanges. In it, even with difficulty, the overcoming is glimpsed as a light at the 'end of the tunnel'. In GA, the bridge/school is a path that leads to the assessment world, which is society. School as one of the bridges to assessment can lead to both positive and negative assessment. Difficulty can be the bridge/path itself (methodology). In the technique of the elements, the fire-type test is red and suffocates, because in its presence there is no air, just as in the air lies the lightness of not evaluating freedom. In this situation, the student can acquire wings and fly through creativity.